What Does Neuroimaging Indicate in Excoriation (Skin-Picking) Disorder? - Atmaca, Murad; Tabara, Muhammed Fatih (Lippincott Williams & Wilkins, 2025)
Learning ObjectivesAfter participating in this CME activity, the psychiatrist should be better able to:center dot Analyze neuroimaging findings to identify and explain structural and functional brain differences associated with SPD, including implications for impulse control, emotional regulation, and motor coordination.Learning ObjectivesAfter participating in this CME activity, the psychiatrist should be better able to:center dot Analyze neuroimaging findings to identify and explain structural and functional brain differences associated with SPD, including implications for impulse control, emotional regulation, and motor coordination.AbstractSkin-picking (excoriation) disorder (SPD), characterized by recurrent and excessive skin picking without underlying skin disease, leads to significant tissue damage. This review highlights the disorder's influences on brain function and structure. Neuroimaging and neurocognitive studies indicate that impairments in frontostriatal circuits are critical to SPD development. Abnormalities in motor control circuits also contribute to motor control issues and impulsivity, suggesting that these circuits play a role in SPD's pathophysiology. Functional imaging studies show hypoactivity in the anterior cingulate cortex, dorsal striatum, and right medial frontal areas, regions essential for motor movement formation and suppression. Structurally, patients with SPD exhibit brain volume and cortical thickness changes in frontal regions involved in impulse control, such as the inferior frontal gyrus, orbitofrontal cortex, and nucleus accumbens, compared to those with trichotillomania and healthy controls. These findings suggest that SPD has distinct neurobiological and neuroanatomical features, emphasizing the importance of further research to understand its underlying mechanisms.
Keywords: excoriation; fMRI; MRI; neuroimaging; skin-picking disorder